Turmeric and Mangosteen Extract Modulate Autophagy Gene Expression in High-Fat Diet-Induced Rats - Gunadi, Julia Windi; Jasaputra, Diana Krisanti; Pangestuti, Balqist Sriprobo; Wahyudianigsih, Roro; Lesmana, Ronny (Faculty of Medicine Universitas Padjadjaran, 2024)
Background: High-fat diet (HFD) increases the risk of obesity, metabolic syndrome, coronary artery disease, and chronic kidney disease, resulting in lipotoxicity. Turmeric and mangosteen are two ingredients mostly used in Indonesian food, and are known for their antihyperlipidemic and antioxidant effects. The aim of this study was to explore the effect of turmeric and mangosteen on autophagy gene expression in HFD-induced kidneys in rats model.Methods: The study was an experimental study, including 25 male Wistar rats aged 8 weeks, divided into 5 groups with a completely randomized design; group with a standard diet as negative control group, the group with a high-fat diet as a positive control group, and the HFD groups with turmeric or mangosteen or fenofibrate. The study was conducted in Maranatha Biomedical Research Laboratory from January to November 2022. Autophagy gene expression (LC3, p62) was measured along with the histopathological scoring to observe necrosis, inflammation, and fat degeneration state. Data was analyzed using One Way ANOVA or Kruskal Wallis and post hoc Least Significant Difference or Mann Whitney.Results: There were significant differences in inflammation in groups treated with mangosteen (p=0.007); in fat degeneration in groups treated with mangosteen and fenofibrate (p=0.007). Furthermore, the LC3 gene expression was increased in all HFD groups as well as the p62 gene expression in group treated with turmeric (p=0.020) and fenofibrate (p=0.005).Conclusions: Mangosteen decreases inflammation and fat degeneration scoring, while turmeric increases autophagy in the kidney of HFD induced Wistar rats.